Towards a new form of undemocratic capitalism: Introducing macro-equity to finance development post COVID-19 crisis - Arvind Ashta (Journal of Risk and Financial Management, 2021)
Sustainable Development Goal 16 talks about Peace, Justice, and Strong Institutions, and goal 10 talks about reducing inequality. A major problem exposed by the COVID-19 crisis is that public deficits seem to be the normal state in the business cycle's booms and downturns, limiting capacity for emergencies. Corporate capitalism has an incentive to perpetuate deficits to increase growth, provide risk-free interest income to financial institutions, and to increase inequalities and economic injustice. To counter this problem, the purpose of this communication is to suggest that countries need to issue equity capital, which we term macro-equity. This macro-equity will give dividends to its shareholders in times of public surplus and issue new shares in times of public deficits. The communication is written as a mind experiment, debating the issues that may arise. This proposal raises many questions of an ethical and moral nature that will lead to passionate debate. The use of macro-equity will reduce countries' stress, created by high public debt. With appropriate incentives, it may create an entrepreneurial mindset in political leaders that may even reduce corruption and promote redistribution. The moral and ethical issues need to be weighed against the street violence in the absence of any change.
Keywords: 330; inequality; capitalism; macro-equity; macroeconomic risk; political entrepreneurship; public debt; public finance